A Transparent, Highly Stretchable, Autonomous Self‐Healing Poly(dimethyl siloxane) Elastomer. Issue 15 (10th May 2017) - Zhang, Baolin; Zhang, Ping; Zhang, Hanzhi; Yan, Casey; Zheng, Zijian; Wu, Biao; Yu, You
Abstract : Autonomous self‐healing poly(dimethylsiloxane) elastomer with high optical transmittance (80%) and stretchability (≈700%) is prepared by simply mixing triformylbenzene and amine‐terminated poly(dimethylsiloxane), showing rapid and efficient self‐healing capability both in air and water over a broad temperature region. As a proof‐of‐concept, such an elastomer is used as the anticorrosion layer, reusable adhesive, and platforms for self‐healing and flexible interconnectors and chemical sensors. Abstract : An innovative self‐healing polydimethylsiloxane (PDMS) elastomer, namely, PDMS‐TFB, is reported by incorporating the reversibly dynamic imine bond as the self‐healing points into the PDMS networks. The PDMS‐TFB elastomer features good optical transmittance (80%) in full visible light region, high stretchability (≈700%), and excellent autonomous self‐healing ability at room temperature. Surprisingly, the self‐healing behavior can take place in water and even at a temperature as low as −20 °C in air, showing a promising outlook for broader applications. As a proof‐of‐concept, this study demonstrates the use of the PDMS‐TFB elastomer for preparing anticorrosion coating and adhesive layer, and also the use of such an elastomer to be the platform for fabricating the flexible interconnector and chemical sensor. Remarkably, no significant difference is observed between the pristine and healed samples. Taking full advantage of these unique properties, it is anticipated that such a PDMS‐TFB elastomer shows wide applications in the fields of materials science, electronics, biology, optics, etc.